ANTIMICROBIAL SUSCEPTIBILITY PATTERNS OF PSEUDOMONAS AEUROGINOSA ISOLATED FROM PATIENTS WITH RESPIRATORY DISEASES IN A TERTIARY CARE HOSPITAL - SAEED , H; RAMZAN , Z; KHAN , AW (Biological and Clinical Sciences Research Journal, 2023)
Antimicrobial medicines have been extensively used since ancient times to treat various microbial infections, many of which can be life-threatening and contribute significantly to healthcare expenses worldwide. However, the increasing adaptability of these antibiotics has led to the emergence of resistance among microorganisms. This study aims to investigate the prevalence and susceptibility patterns of Pseudomonas aeruginosa among patients with respiratory disorders in a tertiary healthcare setting. A cross-sectional study was conducted at Civil Hospital Sialkot from September 2021 to June 2022, where 500 sputum samples were collected from both in and out-patients. Samples were collected following standard protocols and subjected to inoculation. Isolates were identified using standard biochemical protocols, and their antibiotic susceptibility patterns were determined using the Clinical and Laboratory Standards Institute (CLSI) guidelines and Kirby-Bauer’s disc diffusion method. Out of the 500 sputum samples collected, 206 (41.2%) showed growth of microorganisms. Of these, 77 (37.38%) were identified as Pseudomonas aeruginosa. The isolates comprised 54.5% males and 45.5% females, with a mean age of 54.77 ± 11.16. The highest sensitivity was observed for Amikacin (93.5%), followed by Meropenem (92.21%), while the lowest sensitivity was observed for Cefoperazone (18.18%) and Tazocin (16.89%). Similarly, maximum resistance was seen in the case of Cefoperazone and Tazocin at (81.82%) and (83.11%) respectively. The results indicate that commonly used antibiotics against Pseudomonas aeruginosa are becoming increasingly resistant, with aminoglycosides and carbapenems remaining the two classes with the highest activity against this microorganism. These findings underscore the need for continued surveillance and appropriate use of antibiotics to minimize the development of resistance.